Keratin metaplasia in the epithelial lining of odontogenic cysts - Thangadurai Maheswaran; Venkatapathy Ramesh; Nirima Oza; Abikshyeet Panda; P D Balamurali (Wolters Kluwer Medknow Publications, 2014)
Objective: To find the prevalence of keratin metaplasia and its relation with clinico-pathological profile of the odontogenic cyst. Materials and Methods: Odontogenic cysts were studied histologically with special stains to identify the presence of keratin and compared with various parameters such as underlying connective tissue inflammation, average epithelial thickness, and site of the cyst, type of the cyst, age and the sex of the patient. Results: Of 71 cases of various odontogenic cysts, 26 (36.6%) cases exhibited keratinization in the epithelial lining. In cysts with severe inflammation there is absence of keratinization. Conclusions: This study reveals higher prevalence of keratin metaplasia in the odontogenic cysts. Furthermore, inflammation is found to be one of factor influencing keratin metaplasia.